To study the cognitive disorders in patients of young age who suffered from brain stroke - Varahabhatla, Vamsi; Sahithi, Katnam (Одеса : ОНМедУ, 2017)
Aim: to study the cognitive disorders in patients of young age who suffered from brain stroke. Objectives. 1. To assess the state of cognitive functions in young patients who have suffered from brain stroke and patients with vascular disease without stroke in anamnesis. 2. Identification of patients of cognitive decline at earlier stages and their correction. 3. To identify cognitive deficits used short scale mental status Mini Mental State Examination.
Keywords: тези доповідей